Characterisation of vacuum outgassed plastic materials for miniature relays - Koller, Lidija (Informacije MIDEM, 1997)
Vacuum outgassing as a cleaning procedure was introduced and its influence on the contact characteristics and reliability of miniature relays was examined. Three plastic materials: Lexan, Araldit and Ultramid were considered. The conditions of high vacuum ?$(1X10^{-6} mbar)$? and the temperature of 135°C were provided by the laboratory experimental equipment where plastic materials were outgassed for 48 hours. The gas mixture obtained by the outgassing procedure was analysed with the mass spectrometer. Beside other gasses saturated and unsaturated hydrocarbons ?$C_nH_m$? with low number of carbon atoms were detected. The most intensive contamination of the relay atmosphere with hyrocarbons was found for Araldit while the other two materials have rather low outgassing rate therefore its influence on the relay at mosphere contamination is negligible.
Keywords: čiščenje; elektronski merilni instrumenti; masna spektroskopija; razplinjevanje; releji